Convergence of the New Iterative Method - Sachin Bhalekar; Varsha Daftardar-Gejji (International Journal of Differential Equations)
A new iterative method introduced by Daftardar-Gejji and Jafari (2006) (DJ Method) is an efficient technique to solve nonlinear functional equations. In the present paper, sufficiency conditions for convergence of DJM have been presented. Further equivalence of DJM and Adomian decomposition method is established.